Skills That Matter: Qualitative Study Focusing on the Transfer of Training Through the Experience of Thai Vocational Students - Thianthai, Chulanee; Sutamchai, Kunkanit (Frontiers in Education, 2022)
Ensuring the transfer of training and preparing students to gain skills required for their specific professions are at the heart of vocational education and training (VET). Accordingly, school-work alignment is a key determinant in the transfer of training. Today, vocational graduates with mechatronics-based skillsets are highly sought-after. It is thereby crucial for VET to develop relevant pedagogies that can equip students with the skills they need to ensure the transfer of training. Literature has suggested that soft skills are increasingly important, yet rarely has there been research focusing on the lived experiences of vocational students in this field. This study aims to understand the important skills—both hard and soft skills—for vocational mechatronics and robotics students in Thailand through their own experiences, by exploring what skills they acquired from school that are significant to them, and what skills they need when they practise their jobs. The study employed qualitative methods, drawing from 40 semi-structured interviews with vocational mechatronics and robotics students, who are in their last year in dual vocational training programmes from two prominent technical schools in Thailand. Findings reveal that the most significant skills that students acquired from mechatronics and robotics programme were technical knowledge and skills, creative and innovative thinking, teamwork, and perseverance. The most important skills for their future work, interestingly, were all soft skills considered to be necessary when it comes to practical work, namely, language and communication, adaptability and interpersonal skills, willingness to learn, and innovative thinking. Our data also yielded an understanding of some relations across skillsets and the culturally specific meanings ascribed to certain skills and skillsets. This research not only identifies important skills for vocational mechatronics students, but also why those skills are perceived as important and how they are applied in practice. Vocational mechatronics and robotics curriculum should pay more attention to soft skills development to ensure adequate skills of students for their work settings. We recommended that VET across different cultural contexts should explore the meaning and values of skills requirements according to their respective cultural group to make suitable curriculums for their specific contexts.